Direct reuse of scour and bleach effluent water for cotton knitted fabrics - S, Syam Sundar. (The Scientific Temper, 2023)
In a view on Environmental aspects, the amount of the pretreated effluent water from the Textile processing industry is very much harmful to the surroundings of living things and for human beings. The water which has been released from the processing industry contains a chemicals and salts used in the processing of the De-sizing, Scouring, Bleaching and Dyeing. These processes contain high BOD, COD and pHs To evaluate this, the processing mills are having the reuse of the contaminated water by the ETP process which is well known in the world. These ETP’s are helped to reuse the water in the above pretreatment process to overcome the environmental issues. So in this current paper, we had discussed and done the process of reusing the contaminated water taken from the combined scouring & bleaching process for the Knitted fabrics. That processed water can be reused for the next day (knitted sample) and so on. When until the water gets evaporated. We can eliminate reducing the fresh water content for (Hot wash & cold wash) and by adding the required chemicals and salts used for the combined scouring and bleaching process.